2016
DOI: 10.3389/fpsyg.2016.01769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consideration of Schizotypal Traits: A Review

Abstract: Schizotypal traits are of interest and importance in their own right and also have theoretical and clinical associations with schizophrenia. These traits comprise attenuated psychotic symptoms, social withdrawal, reduced cognitive capacity, and affective dysregulation. The link between schizotypal traits and psychotic disorders has long since been debated. The status of knowledge at this point is such schizotypal traits are a risk for psychotic disorders, but in and of themselves only confer liability, with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 142 publications
1
28
0
3
Order By: Relevance
“…The novel extension of these findings to both BD and SZ cases, and the robust associations with the suspiciousness subscale of the SPQ in particular, implicates traumatic experiences in the development of paranoid ideation in both healthy and clinical participant groups. While a large number of genetic markers have been associated with schizotypy (Barrantes‐Vidal, Grant, & Kwapil, ; Walter, Fernandez, Snelling, & Barkus, ), it is plausible that the interplay between genetic and environmental risk factors (e.g., childhood trauma) for psychosis might operate via subtle effects on threat perception (i.e., paranoid ideation), independently of the development of illness. Consistent with Raine's neurodevelopmental model of schizotypal personality (Green, Boyle, & Raine, ; Raine, ), it is also possible that environmental interactions with mild genetic liability for schizophrenia may produce similar phenotypes in adulthood despite different routes to their development.…”
Section: Discussionmentioning
confidence: 99%
“…The novel extension of these findings to both BD and SZ cases, and the robust associations with the suspiciousness subscale of the SPQ in particular, implicates traumatic experiences in the development of paranoid ideation in both healthy and clinical participant groups. While a large number of genetic markers have been associated with schizotypy (Barrantes‐Vidal, Grant, & Kwapil, ; Walter, Fernandez, Snelling, & Barkus, ), it is plausible that the interplay between genetic and environmental risk factors (e.g., childhood trauma) for psychosis might operate via subtle effects on threat perception (i.e., paranoid ideation), independently of the development of illness. Consistent with Raine's neurodevelopmental model of schizotypal personality (Green, Boyle, & Raine, ; Raine, ), it is also possible that environmental interactions with mild genetic liability for schizophrenia may produce similar phenotypes in adulthood despite different routes to their development.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have found that schizotypal traits are present in people without schizophrenia, including offspring with parental psychiatric disorders and the general population (3). Schizotypal traits are of interest and importance in their own right but also have theoretical and clinical relevance to schizophrenia (4). Individuals with schizotypal traits show similar symptoms to schizophrenia patients but to a milder degree.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors argue for a dimensional approach and a continuum between schizotypal traits and schizophrenia spectrum disorder 1 , 11 , 12 ; support for their argument is provided by genetic and linkage studies showing a considerable overlap between genetic association profiles in schizotypy and schizophrenia. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%